Study Some of the Risk Factors on Total Antioxidant Capacity in Iraqi Patients with Sporadic Colorectal Cancer - Moaed E. Al-Gazally (Journal of Global Pharma Technology, 2018)
Colorectal cancer is one of the most frequent malignant diseases in the developed countries. It was reported that total antioxidant status is being play a very important roles in development of carcinogenesis. The aim of this study to assess of some risk factors such as age, gender, obesity, and smoking status on total antioxidant status in patients with sporadic colorectal cancer in Iraq. This investigate was completed by using colorimetric method to measure of total antioxidant capacity (T-AOC) and assess the risk factors depending on the levels of T-AOC. All patients included in the present study were getting adjuvant chemotherapy regimen and subdivided into two groups according to Duke´s classification of malignant into early stages A+B and advance stages C+D, cancer site (colon or rectum), and according to the number of dose of chemotherapy regimen (half dose or total dose). The present study showed negatively correlation (r = -0.567) (p<0.05) between T-AOC and ages of patients with sporadic CRC (p< 0.001). The levels of T-AOC decreased in both ever and never smoking compared to control group (p< 0.05). The results showed highly significant difference (p< 0.001) of T-AOC levels between A+B and C+D groups depending on age. The levels of T-AOC was decreased markedly in patients with ages less than 50 years compared to ages more or equal 50 years in both combination stages A+B and C+D (the higher difference was observed in same age and different state). In conclusion the risk factors that studied in this work may be have the main role to decrease levels of T-AOC and in result will increase the probability of injury with colon and rectal cancer in Iraqi population.Keywords: Total antioxidant capacity, Smoking status, Sporadic Colorectal cancer, Adjuvant chemotherapy, Obesity status